Fast enantioseparation of indole phytoalexins in additive free supercritical fluid chromatography - Kozlov, Oleksandr; Kalíková, Květa; Gondová, Taťána; Budovská, Mariana; Salayová, Aneta; Tesařová, Eva (Journal of chromatography. A, Including electrophoresis and other separation methods, 2019)
A series of chiral indole phytoalexins with potential anticancer and antimicrobial activity were enantioseparated in supercritical fluid chromatography. Two polysaccharide-based chiral stationary phases composed of tris-(3,5-dimethylphenylcarbamate) derivatives of amylose or cellulose coated on 2.5 μm silica particles were successfully used. The influences of the polysaccharide backbone, co-solvent type and co-solvent content in the mobile phase on retention, enantioselectivity and enantioresolution of indole phytoalexins were investigated. Fast baseline separations were achieved for 26 from 27 tested compounds. Amylose-based chiral stationary phase provided higher number of baseline resolutions of the indole phytoalexins than the cellulose-based one. However, certain complementary enantioresolution results towards the studied compounds were observed between the investigated columns. The relationship between structure of the indole phytoalexins and their chromatographic behavior in supercritical fluid chromatography was discussed.
Keywords: indoly; stereoizomerie; chemické techniky analytické; seskviterpeny; Indoles; celulosa; Silicon Dioxide; Sesquiterpenes; Amylose; Solvents; rozpouštědla; Stereoisomerism; superkritická fluidní chromatografie; Chemistry Techniques, Analytical; Cellulose; amylosa; oxid křemičitý; Chromatography, Supercritical Fluid; polysacharidy; Polysaccharides